The Social Construction of Improvement: Continuity and Change in Caribbean Migrants’ Life Stories - Fog Olwig, Karen (Anthropologica, 2022)
Migrants’ social mobility in migration destinations is often measured in terms of "objective" socio-economic indi- cators. These, however, generally say little about migrants’ own hopes and aspirations. This analysis of Caribbean migrants’ life stories argues that "improvement" offers a flexible notion of achievement that, as construed by migrants, may be understood according to a range of cultural rationales, thus enabling them to see themselves as worthy social actors. An ethnographic analysis of migrants’ social construction of improvement there- fore opens up a framework of analysis focusing on individuals’ understanding of migration as a means of societal mobility and social recognition.